Incomplete cost – incomplete benefit analysis in transport appraisal. Issue 6 (2nd November 2018) - Hickman, Robin; Dean, Marco
ABSTRACT: This paper examines the current application of transport appraisal in the UK, in particular exploring the partiality of cost–benefit analysis (CBA) within the wider multi-criteria analysis (MCA) process. It argues that applying a quantitative assessment of the varied impacts of complex transport projects can only be partial within the CBA. Analysis can overlook social, human life, environmental and built environment impacts, and projects can be inconsistent with the planning strategy for an area. The application of CBA is critically reviewed using two case studies: the proposed upgrade of the South Fylde railway line and the Heysham-M6 Link Road, both from North West England. A participatory MCA process is suggested to help improve the process of transport appraisal, as part of an improved public debate on transport investment priorities.